Pengalaman Penggunaan Media Video Call dalam Pelatihan Wicara Siswa Kelas D5a Ddn D5b di SLB B Pangudi Luhur Jakarta Barat - Pardi, Pardi (Sahabat Publikasi, 2024)
In the modern era, communication technology, particularly video calls, has become an integral part of daily life. The global pandemic has compelled education to shift towards remote learning, including speech lessons. This research explores the use of video calls via WhatsApp in teaching speech to grade D5A and D5B students during the pandemic. The teaching method still adopts the MMR Model (Modeling, Mentoring, Reinforcement). This study employs a descriptive approach involving teachers and students as informants. The results indicate that video calls can be an effective solution for speech learning amid face-to-face limitations.